SUSTAINABILITY AND QUALITY: ANALYSIS OF THE BENEFITS OF BEE POLLINATION IN COFFEE - Ventavoli, Daniela Maria Andrade; Rezende, Dalilla Carvalho; de Moraes, Clauciana Schmidt Bueno [UNESP] (RGSA- Revista de Gestao Social e Ambiental, 2024)
Theoretical benchmark: Coffee farming has a productive chain of economic, cultural, historical and social relevance for Brazil. Assisted pollination carried out by bees becomes an alternative in increasing productivity and coffee quality, in addition to contributing to biodiversity. In this context, this work was developed with the objective of analyzing the benefits of pollination by bees in coffee production, verifying the effects on quality by comparing physicochemical parameters of the grains. Method: Coffee samples were collected from two areas from pollinated and non-pollinated coffee trees, grouped together forming a sample for each treatment and subsequently dried in a suspended terrace until reaching 12% humidity. For physicochemical characterization of the grains, analyzes of Soluble solids, thousand grains mass, Titratable acidity, pH, Electrical conductivity, and Coloring were performed. Results and conclusion: In the pollinated area, the values of Soluble solids were higher with 31.49°Brix in raw grains and 23.20°Brix in cherry grains and in the Mass of a thousand grains with 113.35g in the raw grain. In the electrical conductivity, titratable acidity and pH parameters, lower values were observed in the pollinated area in the raw grains. For Coloring, better results were observed in coordinates L: 30.98; a: 0.44; b:11.39 in coffee from an area of assisted pollination. The obtained results were significant in pollinated area in the parameters Soluble solids in raw beans and cherry and in Mass of a thousand beans and Color (coordinate L) only in raw beans, when compared to non-pollinated coffee. Regarding titratable Acidity and Electrical conductivity in pollinated area, better analytical results were observed, which are more representative in terms of grain quality. Research implications: Generate scientific data and a reflection on the importance of pollination in sustainable production and its implications not only for agriculture and society, but for the entire balance of ecosystems. Originality and value: Research carried out at Fazenda Nove de Julho located in the municipality of Altinópolis, SP to verify the contribution of stingless bees to coffee production and the valorization of these pollinators as a decisive factor in increasing the productivity and quality of Brazilian agricultural production.
SUSTENTABILIDADE E QUALIDADE: ANÁLISE DOS BENEFÍCIOS DA POLINIZAÇÃO POR ABELHAS NO CAFÉ
Keywords: Coffee Farming; Meliponas; Physicochemical; Quality; Sustainability